Comprehensive assessment and comparison on nutritional qualities of 39 germplasms Actinidia arguta seeds in Northeast China - Miao Yan; Song Pan; Guanlin Qian; Jiabao Wang; Xiaoman Liang; Tiancheng Ye; Heran Xu; Guang Xin (Journal of Future Foods)
Actinidia arguta fruit is famous for its nutritional value, and we can eat the whole fruit with seeds. However, the nutrition of the seeds has yet to be systematically studied, while the value of seeds as by-products of processed products is worth exploring. Besides, the nutritional composition in distinct germplasms has not been reported. In this study, the nutritional indexes of 39 germplasms A. arguta seeds, including fatty acids, amino acids, minerals, phenolic, flavonoids, and starch had been compared and the correlations of these nutrition also had been explored. The results provided that A. arguta seeds were rich in nutrition. Eight fatty acids were found and the ω-6/ω-3 ratio was 0.07 to 2.01. The total amino acid contents ranged from 9.25 to 29.45 mg/100 g. The largest major mineral element was magnesium (216.62−42 117.22 mg/kg), and the largest trace mineral element was iron (13.05−1 326.48 mg/kg). The phenolic, flavonoids, and starch contents were 1.33−5.82 mg/g, 0.41−0.87 mg/g, 11.29%−31.93%, respectively. There were correlations among nutritional indexes, which had significant differences in 39 germplasms of A.arguta seeds (P < 0.05). In order to assess comprehensive nutrition, using the weighted average score system and one germplasm, CJ No. 1, with superior nutritional quality, was identified. The results of this study will enrich the research content of A. arguta seed, provide theoretical guidance for A. arguta seed to become a dietary supplement, reduce the production and processing waste, and promote the development of A. arguta processing industry.